Hard and brittle material densification detection method based on near-field optical amplitude and phase analysis

Through detection methods based on near-field optical amplitude and phase analysis, combined with nanoindentation and nanoinfrared spectroscopy systems, the problem of low densification detection accuracy and efficiency of hard and brittle materials in the prior art is solved, and high-precision and high-efficiency densification detection is achieved.

CN119619553AActive Publication Date: 2025-03-14DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411811917.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the prior art, when detecting local densification of hard and brittle materials, the accuracy is limited and the efficiency is low, especially the resolution of the Raman spectroscopy method is limited and the scanning time is too long, resulting in inaccurate measurements and low efficiency.

Method used

The detection method based on near-field optical amplitude and phase analysis is adopted to detect hard and brittle materials through nanoindentation and nanoinfrared spectroscopy systems, and the near-field optical amplitude and phase images are obtained by scattering scanning near-field optical microscopy system, and the correspondence between densification rate and near-field amplitude and phase are established, and the densification rate at different positions is calculated.

Benefits of technology

It improves the accuracy and efficiency of densification detection of hard and brittle materials, realizes high-resolution densification detection and non-destructive detection, significantly shortens the detection time and avoids mechanical and thermal drift problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619553A_ABST
    Figure CN119619553A_ABST
Patent Text Reader

Abstract

The invention discloses a hard and brittle material densification detection method based on near-field optical amplitude and phase analysis, which comprises the following steps: firstly, determining scanning parameters of a sample, then obtaining the near-field amplitude or phase of the hard and brittle material sample by using a scanning near-field optical microscopic system, and directly obtaining the corresponding relation between the near-field amplitude or phase and the densification rate. And the densification rates at different positions are further obtained. An optical signal, scattered by the probe, of the surface of a sample is collected and analyzed through the detector for imaging, the imaging resolution mainly depends on the manufacturing precision of the tip of the probe, the curvature radius of the tip of the probe is in the magnitude of 10 nm and exceeds the classic diffraction resolution limit, and therefore high-precision detection can be achieved. And optical signals on the surface of the sample are analyzed, so that the surface of the sample cannot be damaged, and densified nondestructive testing can be realized. The high test efficiency effectively solves the problems of low test efficiency and long-time sample scanning thermal drift caused by low test efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of near-field optical microscopes and optical element defect detection, and in particular to a hard and brittle material densification detection method based on near-field optical amplitude and phase analysis. Background Art

[0002] Fused quartz is a typical representative of hard and brittle materials. Due to its excellent properties such as high hardness, high light transmittance, and good thermal stability, it is widely used in optical devices such as laser inertial confinement fusion (ICF), lasers, and photolithography machines. These extreme application fields have put forward higher requirements for the use of hard and brittle materials. Therefore, in order to manufacture components that meet the use requirements, multiple ultra-precision processing procedures are often required. However, due to the physical properties of hard and brittle materials themselves, it is very easy to produce local densification on the surface and subsurface under the action of external forces in the above-mentioned processing process. On the one hand, the existence of densification will reduce the mechanical properties of hard and brittle materials such as hardness and Poisson's ratio; on the other hand, it will cause differential absorption from the matrix material and affect the optical properties. Therefore, when used in high impact loads or occasions with strict optical performance requirements, the existence of densification will cause a decrease in the service life of hard and brittle material components, and also greatly affect the overall service life of the system.

[0003] At present, there are many mainstream detection methods for local densification of hard and brittle materials. For example, for hard and brittle material fused quartz, Raman spectroscopy is mainly used to evaluate the densification rate by the peak shift of the spectrum. However, the accuracy of Raman spectroscopy in evaluating the densification rate is greatly limited. The first major aspect is that the resolution of Raman spectroscopy measurement is limited. In addition to other factors such as the sample, the resolution of the equipment depends on the wavelength of the laser beam and the microscope objective lens that focuses the laser beam on the sample and collects Raman scattering. Under the test conditions of the current mainstream equipment, the lateral diameter of the focused spot can be controlled at the micron level, and the range of local densification is also in the micron level, which means that the interval between each data point of the Raman spectrum is difficult to control small, which directly affects the resolution of the measurement. At the same time, if you want to obtain a two-dimensional Raman image of the sample, inaccurate measurements will also occur. The second major aspect is that the scanning time is too long and the scanning efficiency is low. This phenomenon occurs because fused quartz is an amorphous non-metallic oxide, and the Raman scattering phenomenon is not significant compared to other materials. Therefore, if you want to obtain Raman spectroscopy data with accurate measurement positions, it takes a long measurement time. As the single-point measurement time increases, not only will the total image scanning time be greatly extended to several hours, but it will also aggravate mechanical drift and thermal drift, affecting the measurement accuracy.

[0004] Therefore, the use of current existing technologies for densification detection is often limited, and it is necessary to find a new optical microscopy-based method to detect the densification of hard and brittle materials. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a hard and brittle material densification detection method based on near-field optical amplitude and phase analysis, which can improve the accuracy and efficiency of hard and brittle material densification detection.

[0006] The technical solution of the present invention is as follows:

[0007] A method for detecting the densification of hard and brittle materials based on near-field optical amplitude and phase analysis comprises the following steps:

[0008] Step 1: Pre-densification by nanoindentation to form a nanoindentation area on the surface of the hard and brittle material with an indentation load of 100 to 500 mN.

[0009] Step 2: Use a nano-infrared spectroscopy system to perform infrared absorption tests on different positions of the nano-indentation area to obtain a nano-infrared spectrum diagram, and determine that the excitation light wavelength that produces the highest peak intensity is the optimal nano-infrared absorption peak.

[0010] Step 3: The scattered scanning near-field optical microscopy system performs a full-range image scan of the nanoindentation area with infrared light of a wave number corresponding to the optimal nano-infrared absorption peak to obtain a near-field optical amplitude and phase scanning image of the nanoindentation area.

[0011] Step 4: extract data from the near-field amplitude and phase scanning images of the indentation area to obtain the variation patterns of the near-field amplitude and phase at different positions of the indentation and the substrate; determine the corresponding relationship between amplitude and phase and densification by exploring the near-field amplitude and phase changes corresponding to different densification rates.

[0012] Step 5: Calculate the densification rate at different positions in the nanoindentation area according to the corresponding relationship between the near-field amplitude and phase and the densification and the variation law of the near-field phase in the nanoindentation area.

[0013] Furthermore, in step 1, the nanoindentation area is prefabricated using a standard Berkovich indenter, and the load is directly controlled by the nanoindenter.

[0014] Furthermore, in step 2, the nano-infrared spectroscopy system detects the thermal expansion of the local sample surface caused by absorbing infrared radiation through the tip. The nano-infrared spectroscopy system includes an atomic force microscope device and an optical device. The tip of the probe of the atomic force microscope device is coated with gold, and the radius of curvature of the tip of the probe is 20-40nm. The probe works in contact mode when performing nano-infrared spectroscopy scanning. The light source of the optical device is a tunable quantum cascade laser, and the harmonic adjustment range of the quantum cascade laser is 940~1900cm -1 .

[0015] Furthermore, the size of the area of ​​the full-range image scan in step three is determined according to the size of the nanoindentation, ensuring that the scanned image contains both the nanoindentation and the surrounding substrate area of ​​appropriate size. The scattering scanning near-field optical microscopy system collects and analyzes the sample near-field signal scattered by the probe through the MCT detector for near-field optical imaging. The scattering scanning near-field optical microscopy system includes an atomic force microscope device and a near-field optical device. The probe of the atomic force microscope device operates in a tapping mode when performing near-field optical imaging. The tip curvature radius of the probe is 20-40nm. The light source of the near-field optical device is a tunable quantum cascade laser or a CO2 laser. According to the optimal nano-infrared absorption peak of the incident light of the sample obtained in step two, a laser containing the wave number corresponding to the optimal nano-infrared absorption peak is selected. The MCT detector is a mercury cadmium telluride detector, which is suitable for optical detection in the infrared field. The reference signal of the near-field amplitude and phase selects the signal of the substrate area without densification area for reference.

[0016] Furthermore, the variation law of the near-field amplitude and phase at different positions in step four is the variation law from the substrate area to the center of the indentation. The correspondence between the near-field phase and densification is jointly established by the first principles and the dipole model method. The specific method is to calculate and obtain the dielectric constant of the hard and brittle material model with different densification rates by the first principles. Further, the calculated dielectric constant information is substituted into the dipole model for solving to obtain the near-field amplitude and phase. The parameters in the dipole model are directly determined according to the relevant parameters during the experiment. The dipole model is a point dipole model or a finite dipole model. By comparing the near-field amplitude or phase obtained by experiment and calculation, it is determined that the scattered scanning near-field optical microscopy system signal that directly reflects the densification rate is an amplitude signal or a phase signal. Then the correspondence between the densification rate and the near-field amplitude or phase is established. The corresponding relationship is compared by comparing the near-field amplitude or phase obtained through experiments and calculations, and then fitting is performed between the densification rate and the near-field amplitude or phase. The fitting relationship is different according to the different change relationships between the densification rate and the near-field amplitude or phase obtained.

[0017] Furthermore, in step five, the correspondence between the near-field phase and the densification is used to substitute the near-field phase at different positions of the indentation, and the densification rate at the corresponding position is inversely calculated.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention can first determine the scanning parameters of the sample, and then use a scanning near-field optical microscope system to obtain the near-field amplitude or phase of the hard and brittle material sample, directly obtain the corresponding relationship between the near-field amplitude or phase and the densification rate, and then obtain the densification rate at different positions.

[0020] 2. The present invention collects and analyzes the optical signals of the sample surface scattered by the probe through the detector for imaging, so the resolution of the imaging mainly depends on the manufacturing accuracy of the probe tip, and the tip curvature radius of the probe is on the order of 10nm, which exceeds the classical diffraction resolution limit, so high-precision detection can be achieved. And because the optical signals on the sample surface are analyzed, the sample surface will not be damaged, and densified non-destructive testing can be achieved.

[0021] 3. The present invention greatly improves the test efficiency. Specifically, compared with the Raman spectrum, which takes about 12 hours to obtain an image of 10μm×10μm with a scanning resolution of 32×32, the present invention takes about 20 minutes to obtain an image of 10μm×10μm with a scanning resolution of 128×128. The higher test efficiency effectively solves the problem of low test efficiency and the thermal drift of samples caused by long-term scanning. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the morphology of the nanoindentation area of ​​the hard and brittle material fused quartz.

[0023] Figure 2 Nano-infrared spectra at different positions in the nanoindentation area of ​​hard and brittle material fused quartz.

[0024] Figure 3 The near-field optical phase image of the nanoindentation region of the hard and brittle material fused silica.

[0025] Figure 4 is the variation trend of the near-field phase at different positions.

[0026] Figure 5 The densification rate results at different positions of the indentation under multiple different loads obtained according to an embodiment of the present invention.

[0027] Figure 6 The densification rates at different indentation positions obtained according to the embodiments of the present invention are compared with those in the literature. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the contents of the present invention will be described more comprehensively in conjunction with the accompanying drawings and embodiments. It should be understood that the embodiments described herein are only used to explain the present invention and are not limited to the present invention. All other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0029] Embodiment 1:

[0030] This embodiment is used to illustrate the densification detection method of hard and brittle material fused quartz.

[0031] Step 1: pre-densification of the hard and brittle material surface by nano-indentation, with an indentation load of 100 to 500 mN, preferably 100 to 250 mN.

[0032] The morphology of the indentation is shown in Figure 1 As shown, the indentation load is 250mN. The surface morphology of the sample is obtained by an atomic force microscope, and the curvature radius of the probe is about 20nm. During the scanning process, the atomic force microscope works in tapping mode, the sampling frequency of the morphology scanning is 1Hz, and the resolution of the scanning morphology is 256×256.

[0033] Step 2: Use a nano-infrared spectroscopy system to perform infrared absorption tests on different positions of the nano-indentation area determined in step 1 to obtain a nano-infrared spectrum, and determine that the excitation light wavelength that produces the highest peak intensity is the optimal nano-infrared absorption peak.

[0034] The nano-infrared spectroscopy system includes an atomic force microscope device and an optical device. The probe of the atomic force microscope device is a gold-coated probe tip, and the tip curvature radius of the probe is about 20nm. The probe works in contact mode when performing nano-infrared spectroscopy scanning. The light source of the optical device is a tunable quantum cascade laser, and the tunable wave number range of the quantum cascade laser is 940 to 1900cm -1 .like Figure 2 As shown in Figure 2, the nano-infrared spectra of the samples were obtained at different positions of the indentation, with a wave number range of 940 to 1250 cm -1 , scanning resolution 2cm -1 From the nano-infrared spectrum data at different positions, it can be seen that when the excitation light wave number is 1070cm -1 When the nano-infrared optical absorption of fused quartz is the most obvious, the spectral peak intensity reaches the highest, so the optimal nano-infrared absorption peak is determined to be 1070cm -1 .

[0035] Step 3: Use the optimal nano-infrared absorption peak determined in step 2 to perform a scattering scanning near-field optical microscopy system scan, perform a full-range image scan on the nanoindentation area determined in step 1, and obtain the near-field optical amplitude and phase results of the area. The reference signal of the near-field amplitude and phase signal selects the signal of the non-densified area of ​​the substrate area for reference.

[0036] Figure 3The near-field phase result of the indentation is shown. The scanning image size is 20×20μm, the scanning image resolution is 256×256, and the scanning sampling frequency is 0.1Hz. The atomic force microscope device is the same system as the atomic force microscope device for nano-infrared spectroscopy. The probe works in tapping mode when performing near-field optical imaging. The light source of the near-field optical device is a tunable quantum cascade laser or a CO2 laser. The MCT detector is a mercury cadmium telluride detector.

[0037] Step 4, extract data from the near-field amplitude and phase scanning images of the indentation area obtained in step 3, and obtain the variation law of the near-field amplitude and phase at different positions such as the indentation and the substrate; by exploring the near-field amplitude and phase changes corresponding to different densification rates, determine the correspondence between amplitude, phase and densification. The specific method is to calculate and obtain the dielectric constant of different densification rate models by first principles. Furthermore, the calculated dielectric constant information is substituted into the dipole model for solution to obtain the near-field amplitude and phase. The parameters in the dipole model can be directly determined according to the relevant parameters during the experiment. The dipole model is a point dipole model or a finite dipole model. The near-field amplitude or phase calculated by the dipole model is compared with the near-field amplitude or phase obtained by the experiment to determine that the scattered scanning near-field optical microscopy system signal that directly reflects the densification rate is a phase signal.

[0038] like Figure 4 The near-field phase edge is shown in Figure 3 The trend of the white line is shown in the figure. It can be seen from the figure that the near-field phase of the substrate remains basically unchanged, while in the inner area of ​​the indentation, as the topography gradually decreases, the phase also gradually decreases, which is caused by the continuous deepening of the densification rate.

[0039] The correspondence between the near-field phase and the densification is established by combining the first principle and dipole model methods. The correspondence between the near-field phase and the densification is:

[0040]

[0041] Where D is the densification rate, is the near-field phase. The corresponding relationship is mainly compared by the near-field phase obtained by experiment and calculation, and the fitting relationship between the densification rate of direct fused quartz and the near-field phase signal is determined to be a quadratic polynomial fitting, and then the densification rate and the near-field phase are fitted. The fitting relationship is different according to the different responses of different detection materials to s-SNOM.

[0042] Step 5: Calculate the densification rate at different positions of the indentation area according to the corresponding relationship between the near-field phase and the densification determined in step 4 and the variation law of the near-field phase in the indentation area.

[0043] like Figure 5 As shown, according to the correspondence between the near-field phase and densification in step four, the densification rates at different positions from the center of the indentation to the edge of the indentation with three different loads of 500mN, 300mN, and 250mN are calculated. The densification rate is highest at the center of the indentation, and gradually decreases with the increase of the distance from the center of the indentation. At the same time, the densification rate obtained by the detection method of the present invention is compared with the densification rate in the literature (Raman spectroscopic measurements and imaging on sub-newton Berkovich and spherical imprints in fused silica, Journal of Non-Crystalline Solids 2024) to verify the correctness of the densification results obtained by the method of the present invention. The comparison results are shown in Figure 2. Figure 6 As shown in the results, it can be seen that the densification rate calculated according to the present invention is in good agreement with that in the literature, which verifies the correctness of the invention.

[0044] The present invention is not limited to this embodiment, and any equivalent concepts or changes within the technical scope disclosed by the present invention are included in the protection scope of the present invention.

Claims

1. A method for detecting the densification of hard and brittle materials based on near-field optical amplitude and phase analysis, characterized in that: The steps include: Step 1: pre-densification by nanoindentation to form a nanoindentation area on the surface of the hard and brittle material with an indentation load of 100 to 500 mN; Step 2: Use a nano-infrared spectroscopy system to perform infrared absorption tests on different positions of the nano-indentation area to obtain a nano-infrared spectrum, and determine that the excitation light wavelength with the highest peak intensity is the optimal nano-infrared absorption peak; Step 3: Using a scattering scanning near-field optical microscope system to perform a full-range image scan of the nanoindentation area with infrared light of a wave number corresponding to the optimal nano-infrared absorption peak, to obtain a near-field optical amplitude and phase scanning image of the nanoindentation area; Step 4: extract data from the near-field amplitude and phase scanning images of the indentation area to obtain the variation law of the near-field amplitude and phase at different positions of the indentation and the substrate; determine the corresponding relationship between the amplitude and phase and the densification by exploring the variation of the near-field amplitude and phase corresponding to different densification rates; Step 5: Calculate the densification rate at different positions in the nanoindentation area according to the corresponding relationship between the near-field amplitude and phase and the densification and the variation law of the near-field phase in the nanoindentation area.

2. According to claim 1, a method for detecting densification of hard and brittle materials based on near-field optical amplitude and phase analysis, characterized in that: The nanoindentation area in step 1 is prefabricated using a standard Berkovich indenter, and the load is directly controlled by the nanoindenter.

3. According to claim 1, a method for detecting densification of hard and brittle materials based on near-field optical amplitude and phase analysis is characterized in that: Step 2: The nano-infrared spectroscopy system detects the thermal expansion of the local sample surface caused by absorbing infrared radiation through the tip; the nano-infrared spectroscopy system includes an atomic force microscope device and an optical device; the tip of the probe of the atomic force microscope device is coated with gold, and the tip curvature radius of the probe is 20-40nm; the probe works in contact mode when performing nano-infrared spectroscopy scanning; the light source of the optical device is a tunable quantum cascade laser, and the harmonic adjustment range of the quantum cascade laser is 940-1900cm -1 .

4. The method for detecting the densification of hard and brittle materials based on near-field optical amplitude and phase analysis according to claim 1, characterized in that: The size of the area for the full-range image scanning in step 3 is determined according to the size of the nanoindentation, ensuring that the scanned image simultaneously includes the nanoindentation and the surrounding substrate area of ​​appropriate size; the scattering scanning near-field optical microscopy system collects and analyzes the sample near-field signal scattered by the probe through the MCT detector for near-field optical imaging; the scattering scanning near-field optical microscopy system includes an atomic force microscope device and a near-field optical device; the probe of the atomic force microscope device works in a tapping mode when performing near-field optical imaging; the tip curvature radius of the probe is 20-40nm; the light source of the near-field optical device is a tunable quantum cascade laser or a CO2 laser, and according to the optimal nano-infrared absorption peak of the incident light of the sample obtained in step 2, a laser containing the wave number corresponding to the optimal nano-infrared absorption peak is selected; the MCT detector is a mercury cadmium telluride detector, which is suitable for optical detection in the infrared field; the reference signal of the near-field amplitude and phase selects the signal of the non-densified area in the substrate area for reference.

5. The method for detecting densification of hard and brittle materials based on near-field optical amplitude and phase analysis according to claim 1, characterized in that: The variation law of the near-field amplitude and phase at different positions in step 4 is the variation law from the substrate area to the indentation center; the correspondence between the near-field phase and densification is jointly established by the first principle and dipole model methods; the specific method is to calculate and obtain the dielectric constant of the hard and brittle material model with different densification rates by the first principle; further, substitute the calculated dielectric constant information into the dipole model for solution to obtain the near-field amplitude and phase; the parameters in the dipole model are directly determined according to the relevant parameters during the experiment; the dipole model is a point dipole model or a finite dipole model; by comparing the near-field amplitude or phase obtained by experiment and calculation, it is determined that the scattered scanning near-field optical microscopy system signal that directly reflects the densification rate is an amplitude signal or a phase signal; then establish the correspondence between the densification rate and the near-field amplitude or phase; the correspondence is compared by comparing the near-field amplitude or phase obtained by experiment and calculation, and then the densification rate and the near-field amplitude or phase are fitted, and the fitting relationship is different according to the different variation relationship between the obtained densification rate and the near-field amplitude or phase.

6. The method for detecting densification of hard and brittle materials based on near-field optical amplitude and phase analysis according to claim 1, characterized in that: In step five, the correspondence between the near-field phase and the densification is used to substitute the near-field phase at different positions of the indentation, and the densification rate at the corresponding position is inversely calculated.

Citation Information

Patent Citations

  • Hard and brittle material efficient grinding process parameter optimization method

    CN115510627A

  • Peakforce Photothermal-Based Detection of IR Nanoabsorption

    US20140289912A1

  • Method and Apparatus for Infrared Scattering Scanning Near-field Optical Microscopy

    US20160003868A1

  • Method and Apparatus for Infrared Scattering Scanning Near-field Optical Microscopy with High Speed Point Spectroscopy

    US20170003316A1

  • Method and aparatus for infrared scanning near-field optical microscopy based on photothermal effect

    US20180259553A1

Cited By

  • Method and system for improving mass spectrum resolution of three-dimensional atom probe of metal material based on laser polarization and field enhancement effect

    CN120294124A

  • S-SNOM subsurface defect fine imaging method and system based on polarization laser scattering guidance

    CN121830721A

  • A s-snom sub-surface defect fine imaging method and system based on polarization laser scattering guidance

    CN121830721B